Dampak Pandemi Covid-19 terhadap Sistem Pembelajaran - Vita Loka, Oktaria (Yayasan Sembilan Pemuda Indonesia, 2021)
The Covid-19 pandemic has had both a positive and negative effect on Indonesia's educational system. The aim of this article is to explain some of the effects of the Covid-19 pandemic on Indonesia's educational system. The research was carried out by observation and a review of the literature. The Covid-19 pandemic has accelerated progress in the use of internet-based technology in the world of education, especially in online learning.